36 Evaluation and implementation of the heart failure virtual consultation – a powerful tool for the delivery of expert care and the democratisation of knowledge in the community. (October 2018) - Keane, C; Ledwidge, M; Hammond, M; Gallagher, J; Mc Cleland, S; McDonald, K
Abstract : Introduction: As a chronic illness, Heart Failure (HF) should ideally be managed in the community setting with ease of access to specialist opinion and investigations at critical stages of the illness. A recent national GP survey has highlighted problems with access to specialist investigations and opinion as well as comfort in managing HF. More recently we have carried out a project looking forensically at HF pathways and in particular at the barriers to optimal interaction between primary and secondary care. From this work we have developed the Heart Failure Virtual Consultation concept (HFVC), a method of primary-secondary care interaction characterised by on-line, real time, interactive case discussion between the GP and the specialist team. The HFVC provides access for GPs to specialist opinion and thus assists with the management of patients in the community. Importantly the HFVC also facilitates GP empowerment and education by providing support within the community thus reducing the need for secondary/tertiary care referrals. The HFVC is distinct from other eHealth initiatives as it has a dual function. Not only does it provide an appropriate health care intervention but also acts as a system for knowledge dissemination and improving GP confidence levels. This work reports on the initial experience with this intervention in terms of impact on patients outcomes and the view of the GP. Method: The clinic utilises a Skype-like software. GPs refer cases which are prepared in Powerpoint format with anonymised information and returned to the GP for presentation at the clinic. GPs are asked where they would have referred the GP if the HFVC were not available. At the end of the clinic reports of the decision are sent to the GP. To assess the impact of the HFVC on GP capacities and their comfort in HF care an online questionnaire was distributed to users and returned anonymously. Results: The HFVC is available in two geographical regions. From December 2016 -to date the clinic has been used to discuss 610 cases; 60% being first consultations and 40% being follow-up consultations. These cases have been referred by 76 GPs. Case questions have dominantly related to diagnostic and therapeutic challenges. Based on the GPs stated intentions, 22% of cases discussed would have been sent to the acute services, 61% to general outpatient clinics and the remaining 17% would have remained within the primary care system with no onward referral. Following the HFVC, 1% of the patients were referred to the acute services and 8% to general outpatient clinics, representing a significant reduction in use of acute and general OPD services. In the month following the HFVC only one patient has required unanticipated hospital admission. The questionnaire response indicated overwhelming positive view on the clinical usefulness of the HFVC and on the impact of the clinic on GP level of comfort. For example, 83% of GPs said 'The HFVC had impacted their ability to identify HF patients to a high degree', 80% said 'Due to participation in the HFVC they are now very competent in their ability to treat HF patients and manage side effects'. In relation to usability and technology, 100% if respondents 'Found participating in the clinic easy'. Patient testimonials indicated strong positive reaction to the service and appreciation of the efforts to avoid needless travel. In that regard the HFVC has saved approximately 21, 000 Km in patient travel through avoiding referral to secondary services. Discussion: This strong preliminary experience indicates that the HFVC will likely fill a major need in improving doctor-doctor communication between primary and secondary care. The impact on patient outcomes, the improved confidence of GPs with the routine aspects of HF care and the positive impact on the patient through avoiding unnecessary travel indicate that this approach is ideally suited for maintaining patient well-being in the community. Wider use of this platform to include education classes form allied health care professionals will likely further enhance the benefits within HF care while the process is likely also of benefit in the management of other chronic diseases.